Animal nutrition - McDonald, Peter, 1926-2018; Edwards, R. A.; Greenhalgh, J. F. D.; Morgan, C. A. (Animal nutritionist); Sinclair, L. A. (Liam A.); Wilkinson, R. G. (Robert G.)
"Recent research in the field of animal science has focused on advances in molecular biology, particularly in the study of gene expression, epigenetics and gene editing, and exciting advances have been made. However, knowledge of animal biochemistry and nutrition is still essential if we are to understand the significance and efficient application of these new findings to further improve animal production, health and welfare. The application of research and advice in animal nutrition continues to be at the centre of efficient animal production. Research in dog and cat nutrition has also progressed since the last edition and information in this area has been expanded in this new edition. We have retained the early chapters on basic food chemistry and animal biochemistry to provide a quick reference to questions pertaining to the discipline of nutrition chemistry in later parts of the book. We have also taken the opportunity to introduce nutritional topics related to molecular biology and the environment. Each chapter now has a set of questions to assist with revision of the chapter topic and the Appendix tables have been revised where new data are available. Two significant events have occurred since the last edition. In 2016, the British Society of Animal Science recognised the 50th anniversary of the publication of the first edition of Animal Nutrition by awarding framed certificates of congratulation to the original three authors, Peter McDonald, James Greenhalgh and Alun Edwards. Then, in 2018, came the sad news that Peter McDonald had died. Although Peter had not been actively involved in the production of recent editions of the book, he had always shown great interest in its progress. Fittingly, Peter's funeral service was conducted by another eminent animal nutritionist, Rev. Dr. Neville Suttle. The production of this edition was assisted by comments and suggestions received from reviewers and we welcome comments from readers. As with previous editions, we are grateful to colleagues for their helpful discussions"--